Hyperspectral Imaging Surface Analysis for Dried and Thermally Modified Wood: An Exploratory Study. (14th November 2018) - Myronycheva, Olena; Sidorova, Ekaterina; Hagman, Olle; Sehlstedt-Persson, Margot; Karlsson, Olov; Sandberg, Dick
Abstract : Naturally seasoned, kiln-dried, and thermally modified wood has been studied by hyperspectral near-infrared imaging between 980 and 2500 nm in order to obtain spatial chemical information. Evince software was used to explore, preprocess, and analyse spectral data from image pixels and link these data to chemical information via spectral wavelength assignment. A PCA model showed that regions with high absorbance were related to extractives with phenolic groups and aliphatic hydrocarbons. The sharp wavelength band at 2135 nm was found by multivariate analysis to be useful for multivariate calibration. This peak represents the largest variation that characterizes the knot area and can be related to areas in wood rich in hydrocarbons and phenol, and it can perhaps be used for future calibration of other wood surfaces. The discriminant analysis of thermally treated wood showed the strongest differentiation between the planed and rip-cut wood surfaces and a fairly clear discrimination between the two thermal processes. The wavelength band at 2100 nm showed the greatest difference and may correspond to stretching of C=O-O of polymeric acetyl groups, but this requires confirmation by chemical analysis.